ALDOSTERONE AND OBESITY: WHERE TO LOOK FOR THE KEY TO THERAPY? - N. T. Vatutin; A. M. Shevelyok; G. E. Degtiarova (SINAPS LLC, 2016)
For a long period of time adipose tissue was regarded as nonfunctioning 'store' of triglycerides. In our day and age there are enough evidence which confirm that, beside being a main source of energy, adipose tissue is an active endocrine organ, which plays a crucial role in maintaining homeostasis and taking part in the pathogenesis of many diseases. It`s excess is accompanied with hyperactivation of local renin-angiotensin-aldosterone system, increasing of local and systemic concentration of aldosterone and eventually leads to formation of secondary hyperaldosteronism. Aldosterone, in turn, has a direct effect on adipose tissue through a large number of mineralocorticoid receptors expressed on the surface of adipocytes. This leads to an accelerated maturation of the adipose cells and further increase in the amount of adipose tissue Reaching systemic circulation and influencing other organs, the excess of the hormone leads to the insulin resistance, atherosclerosis and progression of systemic inflammatory reactions. The role of aldosterone in the onset and progression of all components of metabolic syndrome - obesity arterial hypertension, glucose metabolism and dyslipidemia - are analyzed in this article. The possibility of usage of selective and non-selective antagonists of the mineralocorticoid receptor in complex treatment of patients with obesity is discussed. Who knows, maybe their usе will become a key to the preventing of the obesity-associated complications.